The Correlation Between Depression and Life Quality of Pregnant Mothers with Preeclampsia in Lumajang District - Andrita Asida (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
Preeclampsia is a specific hypertensive disease in pregnancy with multi-organ involvement. It usually occurs around 20 weeks of gestation and before delivery. The condition of pregnancy with preeclampsia makes the mother more susceptible to experiencing psychological disorders, one of which is depression. Depressive disorders experienced during pregnancy can affect the baby's health condition. Psychological disorders in the form of depression can cause individuals to have a poor quality of life. This study aimed to analyze the relationship between depression and the quality of life of pregnant women with preeclampsia in Lumajang Regency. The research design uses a correlational study with a cross-sectional approach. The study was conducted on 54 pregnant women with preeclampsia in Lumajang District using a total sampling technique. Data collection using a depression questionnaire with quality of life. The results showed that most of the respondents experienced symptoms of depression, namely as many as 42 respondents (77.8%), and half of the respondents experienced a poor quality of life, namely as many as 37 respondents (68.5%). The bivariate analysis using Spearman Rank found a significant relationship between depression and the quality of life of pregnant women with preeclampsia in Lumajang Regency with a value (p-value <α = 0.0001 <0.05). This research implies that the role of nurses needs to conduct assessments and detect depressive symptoms and physical problems earlier to improve patients' quality of life.